PERBEDAAN WAKTU REAKSI VISUAL ANTARA INDEKS MASSA TUBUH KATEGORI UNDERWEIGHT, NORMAL DAN OVERWEIGHT PADA SISWA SEKOLAH DASAR SARASWATI TABANAN - Ni Kadek Ira Maharani Putri; Ari Wibawa; I Dewa Ayu Inten Dwi Primayanti (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACTThis study was to determine the difference of visual reaction time based on underweight, normal and overweightbody mass index’s categories among student at Saraswati elementary school in Tabanan. This study design is across-sectional analytic study held on March 2017. Samples was selected using total sampling technique with totally228 samples which divided into 3 groups based from their body mass index. Normality test using Kolmogorov-smirnovTest and homogeneity test using Levene’s Test had been done (p>0.05). Descriptive analytic show the visual reactiontime in underweight BMI 569,4+50,08 ms, normal BMI 405,31+41,54 ms and overweight BMI 556,75+46,86 ms. Analysisusing One Way ANOVA find out significant mean differences between group (p=0,000) Based on this study, concludethat underweight and overweight children had a longer visual reaction time than normal weight children in SaraswatiElementary School Tabanan.Keywords : Visual Reaction Time, Body Mass Index